Detection of oxygen addition peaks for terpendole E and related indole–diterpene alkaloids in a positive‐mode ESI‐MS. (21st May 2014) - Hongo, Yayoi; Nakamura, Takemichi; Takahashi, Shunya; Motoyama, Takayuki; Hayashi, Toshiaki; Hirota, Hiroshi; Osada, Hiroyuki; Koshino, Hiroyuki
<x xml:space="preserve">Abstract</x> This report describes that a regular positive electrospray ionization mass spectrometry (MS) analysis of terpendoles often causes unexpected oxygen additions to form [M + H + O]+ and [M + H + 2O]+, which might be a troublesome in the characterization of new natural analogues. The intensities of [M + H + O]+ and [M + H + 2O]+ among terpendoles were unpredictable and fluctuated largely. Simple electrochemical oxidation in electrospray ionization was insufficient to explain the phenomenon. So we studied factors to form [M + H + O]+ and [M + H + 2O]+ using terpendole E and natural terpendoles together with some model indole alkaloids. Similar oxygen addition was observed for 1, 2, 3, 4‐tetrahydrocyclopent[b]indole, which is corresponding to the substructure of terpendole E. In tandem MS experiments, a major fragment ion at m/z 130 from protonated terpendole E was assigned to the substructure containing indole. When the [M + H + O]+ was selected as a precursor ion, the ion shifted to m/z 146. The same 16 Da shift of fragments was also observed for 1, 2, 3, 4‐tetrahydrocyclopent[b]indole, indicating that the oxygen addition of terpendole E took place at the indole portion. However, the oxygen addition was absent for some terpendoles, even whose structure resembles terpendole E. The breakdown curves characterized the tandem MS features of terpendoles. Preferential dissociation into m/z 130 suggested the protonation tendency at the indole site. Terpendoles that are preferentially protonated at indole tend to form oxygen addition peaks, suggesting that the protonation feature contributes to the oxygen additions in some degrees. © 2014 The Authors. Journal of Mass Spectrometry published by John Wiley & Sons, Ltd.